A Simple U-Diffusion Inpainting Structure - Montalvão, Jugurta; Bastos, Gabriel F. A.; Filho, Israel J. Santos (Journal of the Brazilian Computer Society, 2026)
The inpainting problem is addressed in this work through a very simplified version of the approach based on low-dimensional manifold model (LDMM), in which the actual working principle of the LDMM is put into evidence, namely, the simulated diffusion of image pixels that takes place in a manifold from which patches are drawn to form a given image. The simplicity of this principle is translated into a straightforward algorithm that borrows ideas from the Locally Linear Embedding (LLE) method, commonly used for dimensionality reduction and data visualization. The equivalence between this much simpler algorithm and the original LDMM is illustrated through visual inspection and experimental measurements of peak signal-to-noise ratios. By maintaining the key components of LDMM while reducing conceptual and computational complexity, the proposed method offers a streamlined solution for image inpainting tasks. Additionally, a (U-shaped) multi-scale use of the proposed algorithm is presented as a significantly better initializer for missing pixels, thus reducing the number of algorithmic iterations for convergence.